Titik Singgung Hukum Administrasi Negara dan Pidana Dalam Pencegahan Tindak Pidana Korupsi - Titi Tantri; Wulandari, Laely (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the role of State Administrative Law in preventing corruption, examine Criminal Law in prosecuting corruption crimes, and identify normative points of intersection between State Administrative Law and Criminal Law for integrated corruption eradication. This study is a normative legal research with a statutory and conceptual approach. Legal materials include primary, secondary, and tertiary legal materials, analyzed through grammatical, systematic, and teleological interpretations, as well as legal theory and legal principles, including the principles of legality, legal certainty, accountability, transparency, and the principles of good governance. This study aims to analyze the role of State Administrative Law in preventing corruption, examine Criminal Law in prosecuting corruption crimes, and identify normative points of intersection between State Administrative Law and Criminal Law for integrated corruption eradication. This study is a normative legal research with a statutory and conceptual approach. Legal materials include primary, secondary, and tertiary legal materials, analyzed through grammatical, systematic, and teleological interpretations, as well as legal theory and legal principles, including the principles of legality, legal certainty, accountability, transparency, and the principles of good governance.